The Action of the Invisible God: New Analogies for Thinking the Trinitarian Mystery - Ruiz Soler, Marcos (Razón y fe, 2026)
Theology has historically drawn upon various analogies to articulate the mystery of the Triune God. This study continues along that path, proposing new analogies inspired by contemporary developments in science. It specifically explores the role of the Divine Persons in the constitution of reality, in light of the profound interrelation between matter, energy, and information as foundational structures of the cosmos. Building on this framework, the article establishes a correspondence between each Person of the Trinity and one of the Aristotelian causes, thereby offering an integrated ontological perspective on divine action. Finally, it examines how each Person contributes uniquely to the ultimate purpose of all creation, revealing the teleological orientation of the universe toward full communion with the God who is Love.